Embryonic Signaling Pathways and Rhabdomyosarcoma: Contributions to Cancer Development and Opportunities for Therapeutic Targeting - Belyea, Brian (Hindawi Publishing Corporation, 2012)
Rhabdomyosarcoma is the most common soft tissue sarcoma of childhood and adolescence, accounting for approximately 7% of childhood cancers. Current therapies include nonspecific cytotoxic chemotherapy regimens, radiation therapy, and surgery; however, these multimodality strategies are unsuccessful in the majority of patients with high-risk disease. It is generally believed that these tumors represent arrested or aberrant skeletal muscle development, and, accordingly, developmental signaling pathways critical to myogenesis such as Notch, WNT, and Hedgehog may represent new therapeutic targets. In this paper, we summarize the current preclinical studies linking these embryonic pathways to rhabdomyosarcoma tumorigenesis and provide support for the investigation of targeted therapies in this embryonic cancer.